STRATEGI PEMASARAN DALAM MENINGKATKAN JUMLAH NASABAH ASURANSI SYARIAH (Studi Kasus: Asuransi Sinar Mas Kantor Pemasaran Bukittinggi) - Nuradila Lutfia; Zulhelmi (CV. Adiba Aisha Amira, 2025)
Asuransi Sinar Mas Marketing Office Bukittinggi is a general insurance company that has an Islamic unit. The Islamic system and products have been available since 2010, following the establishment of its office in Bukittinggi in 2009. Its activities include the marketing and distribution of Islamic insurance and reinsurance products. As the financial industry continues to grow, Islamic insurance has significant potential to expand and become the primary choice for the Muslim community. However, to achieve success, Islamic insurance companies must be able to develop comprehensive and targeted marketing strategies. Through effective marketing strategies, Islamic insurance is expected to continue growing and providing substantial benefits to society, both financially and spiritually. The research problem in this study is how marketing strategies can increase the number of customers of Islamic Insurance at Asuransi Sinar Mas Marketing Office Bukittinggi. The objective of this research is to identify the marketing strategies used to increase the number of customers at Asuransi Sinar Mas Marketing Office Bukittinggi. The research method employed is qualitative research using SWOT analysis, with key informants consisting of the Branch Manager and Marketing Admin at Asuransi Sinar Mas Marketing Office Bukittinggi. Data collection techniques include interviews, observations, and documentation. Based on the research findings, the marketing strategy to increase the number of Islamic insurance customers at Asuransi Sinar Mas Marketing Office Bukittinggi is through the SO (Strengths-Opportunities) strategy. The company implements the SO strategy through the following approaches: Utilizing competitive and affordable premium pricing to attract the majority of the Muslim community in Bukittinggi, Enhancing customer service to reach locations near office areas, Simplifying the registration and claims process for traders facing high business risks, Developing digital-based products to leverage the increasing public awareness of Islamic insurance and Integrating Islamic principles into digital products to support technological advancements in marketing.